Bimetallic Catalysis: Palladium/Lanthanide co‐Catalyzed Allylation of Anilines. Issue 6 (24th March 2017) - Šolić, Ivan; Reich, Dominik; Lim, Jieyan; Bates, Roderick W.
Abstract: The direct palladium catalyzed N ‐allylation of anilines by underivatized allyl alcohols can be achieved using lanthanide co‐catalysis. The reaction works equally well with different lanthanides. Surprisingly, lanthanum acetate and lanthanum chloride can give yields comparable to or better than those obtained using lanthanum triflate. Electron‐rich, unhindered anilines are the best substrates, although an aminopyridine and benzimidazole are both also efficiently allylated. Abstract : Bimetallic catalysis using palladium(0) and lanthanum(III) allows N‐allylation with underivatized allyl alcohols. Electron‐rich, unhindered anilines are the best substrates, although an aminopyridine and benzimidazole are both also efficiently allylated.